Evaluasi Kinerja Lalu Lintas Sebelum dan Setelah Pembangunan Underpass Dewi Sartika Kota Depok dengan Metode Simulasi Vissim - Damayanto, Antono; Agus Juhara; Reynaldi Muhamad A.; Akbar Abde Wiansyah (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2024)
Traffic generation or attraction due to construction activities increases the impact of congestion around it. The construction of an underpass at the intersection of Jl. Dewi Sartika Depok with a length of 975m is needed to reduce the density that occurs. The purpose of the study was to evaluate the condition of the existing intersection compared to after the construction of the underpass. The intersection analysis methodology used PKJI 2023 and Vissim simulation modeling. The evaluation results showed the value of the degree of saturation of the existing condition of the Naming Bothin intersection 0.840, Kartini intersection 0.910, and Siliwangi intersection 0.390. After the construction of the underpass, there was a decrease in vehicle volume of 35.02% on 5 road sections, namely Dewi Sartika, Naming Bothin, Kartini, Margonda, and Siliwangi. Vehicle delay at the Naming Bothin intersection 81.07%, Kartini intersection 31.66%, and Siliwangi intersection 6.42%.